FIRST SUPERNOVAE IN DWARF PROTOGALAXIES - Vasiliev, E. O.; Vorobyov, E. I.; Shchekinov, Yu. A. (Одеські астрономічні публікації, 2008)
Using a two-dimensional hydrodynamics code with axial symmetry we explore the chemical, thermal, and dynamical evolution of a shell formed by a high-energy supernova explosion (1053 erg) in dwarf protogalaxies with a total (dark matter plus baryonic) mass 107 Msun at a redshift z = 12. We consider two initial con gurations for the baryonic matter, one without rotation and the other having the ratio of rotational to gravitational energy β = 0.17. The (non-rotating) dark matter halo is described by a quasi-isothermal sphere. We find that the dynamics of the shell is different in protogalaxies with and those without rotation. For instance, the Rayleigh-Taylor instability in the shell develops faster in protogalaxies without rotation. The fraction of a blown-away baryonic mass is approximately twice as high in models with rotation than in models without rotation. We argue that these differences are caused by different initial gas density profiles in non-rotating and rotating protogalaxies. On the other hand, the chemical evolution of gas in protogalaxies with and without rotation is found to be similar. The relative number densities of molecular hydrogen and HD molecules in the cold gas (T ≤ 103 K) saturate at typical values of 10-3 and 10-7, respectively. The clumps formed in the fragmented shell move with velocities that are at least twice as high as the escape velocity. The mass of the clumps is ≈ 0.1-10 Msun, which is lower than the Jeans mass.